Comparative morphological and photosynthetic studies on three Malaysian species of Pogonatum from habitats of varying light irradiances - Nasrulhaq-Boyce, A.; Mohamed, M.A.H.; Lim, A.L.; Barakbah, S.S.; Yong, K.T.; Nor, D.M. (2011)
Comparative morphological and physiological studies were carried out on three species of Malaysian Pogonatum collected from habitats exposed to different light intensities ranging from 28 +/- 4 W/m(2) for P. cirratum subsp. macrophyllum (Dozy & Molk.) Hyvonen, to 230 +/- 39 W/m(2) for P. subtortile (Mull.Hal.) A. Jaeger to 751 +/- 45 W/m(2) for P. neesii (Mull.Hal.) Dozy. Total chlorophyll and beta-carotene content were higher in P. cirratum subsp. macrophyllum and P. subtortile than in P. neesii when calculated on a fresh weight basis. However, soluble protein content was higher in the sun species compared to its shade-adapted counterparts, and the soluble protein to total chlorophyll ratio was highest in P. neesii. The chloroplasts in the leaves of P. cirratum subsp. macrophyllum were significantly larger than those in the other two species, and had more grana and thylakoids per chloroplast profile. The numbers of starch grains in P. cirratum subsp. macrophyllum and P. subtortile were more than double that observed in P. neesii. Morphological studies of the leaves showed specific differences in the shapes and heights of the lamellae found on the adaxial surfaces of the leaves. The lamellae of P. cirratum subsp. macrophyllum were rudimentary whilst those of P. subtortile were 2-3 cells high and P. neesii possessed lamellae 5-7 cells high. These findings indicate a direct correlation between the height of the lamellae and the light irradiances received by the plants. Determination of the in vitro Photosystem II photochemical rates, with an oxygen electrode, of chloroplasts isolated from these plants, showed that P. neesii and P. subtortile exhibited higher rates than P. cirratum subsp. macrophyllum. Similarly in vivo light saturation studies with an infrared gas analyzer showed that CO(2) assimilatory rates were highest in P. neesii, even at low light intensities, suggesting a relationship between photosynthesis and light irradiance in these mosses that is different from vascular plants.